2015
DOI: 10.1053/j.jvca.2014.10.027
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Hypercapnia as a Predictor of Hypotension During Anesthetic Induction in Lung Transplant Recipients

Abstract: Hypotension during anesthetic induction is common in lung transplant recipients, and is independently predicted by preoperative hypercapnia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Finally, ABG demonstrating increased PaCO 2 >55 mm Hg was associated with an increased incidence of hypotension (75%) compared with patients with PaCO 2 <55 mm Hg (31%) during induction of anesthesia for lung transplantation surgery. 11 After adjusting for confounding factors, Mizota et al 11 showed that the odds ratio for the relationship between preoperative hypercapnia and hypotension during anesthetic induction was 12.54 (95% CI = 3.10-66.66). Hypercapnia indicates reduced lung compliance 12 and the presence of hypercarbia in PAH patients may work negatively to precipitate hemodynamic compromise during induction for lung transplantation.…”
Section: Predicting Induction Eventsmentioning
confidence: 99%
“…Finally, ABG demonstrating increased PaCO 2 >55 mm Hg was associated with an increased incidence of hypotension (75%) compared with patients with PaCO 2 <55 mm Hg (31%) during induction of anesthesia for lung transplantation surgery. 11 After adjusting for confounding factors, Mizota et al 11 showed that the odds ratio for the relationship between preoperative hypercapnia and hypotension during anesthetic induction was 12.54 (95% CI = 3.10-66.66). Hypercapnia indicates reduced lung compliance 12 and the presence of hypercarbia in PAH patients may work negatively to precipitate hemodynamic compromise during induction for lung transplantation.…”
Section: Predicting Induction Eventsmentioning
confidence: 99%
“…One contribution is the adoption of the ICV as a PIHI index by merging the various hemodynamic changes after intubation. In previous literatures, most of the attentions were focused on the postoperative outcomes [ 6 8 , 13 , 16 18 , 20 ] and perioperative binary judgement on specific symptom using classification models [ 10 , 11 , 15 , 19 ]. However, few studies have attempted to quantify the post-intubation anesthetic risk with continuous value and build up the prediction model.…”
Section: Discussionmentioning
confidence: 99%
“…Data-driven analysis and machine-learning models have become possible with increasingly structured data, such as preoperative electronic health/medical records [6]. Recently, various models have been developed to predict postoperative mortality [6,7], postoperative pain [8], surgical acceptance [9], hypotension during anesthesia [10][11][12], surgery time [13,14], intraoperative bradycardia [15], postoperative delirium [16,17] and other risk outcomes [18][19][20]. Nevertheless, there is a paucity of endeavors dedicated to preoperative prediction of postintubation hemodynamic instability (PIHI), despite its critical significance in enhancing the perioperative anesthesia quality and safety, as well as mitigating postoperative risks [21].…”
Section: Introductionmentioning
confidence: 99%